2020
DOI: 10.1016/j.cegh.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A study on knowledge and self-care practices about Diabetes Mellitus among patients with type 2 Diabetes Mellitus attending selected tertiary healthcare facilities in coastal Karnataka

Abstract: To assess knowledge and self-care practices about Diabetes among patients with type 2 Diabetes Mellitus attending selected tertiary health care institutions. Methods: Cross-sectional study was conducted to assess the knowledge and self-care practices about Diabetes among diagnosed Type 2 Diabetes Mellitus patients attending the outpatient facilities of Medicine Department at selected tertiary healthcare institutions of Udupi Taluk. The data collection occurred from January to March 2017. A total of 166 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Two studies reported the mean number of days in a week participants were physically active, ranging from 4.08 to 4.23 days [ 20 , 45 ]. Additionally, four studies reported the mean score for physical activity ranging from 3.74 to 5.1 (scale range of 0-10, where 10 represents the optimal practice of self-care) [ 73 , 76 , 86 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported the mean number of days in a week participants were physically active, ranging from 4.08 to 4.23 days [ 20 , 45 ]. Additionally, four studies reported the mean score for physical activity ranging from 3.74 to 5.1 (scale range of 0-10, where 10 represents the optimal practice of self-care) [ 73 , 76 , 86 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dependence on own funds and being diagnosed from a private hospital also negatively affected general diet self-care in diabetic patients [1,10]. Diabetes being a chronic disease, its lifelong treatment and diet entail a substantial expenditure [2,3] Thus if patients had to use their own funds for treatment, they generally found it difficult to purchase such food items as were recommended for good dietary practices, for example, fruits and vegetables whose costs at times could be pretty high. It has been commonly observed that physicians in private practice and in private hospitals lay more emphasis on curative rather than on preventive aspects of management [3].…”
Section: Resultsmentioning
confidence: 99%
“…The Nepalese health care system is struggling to provide all-inclusive services and quality treatment for diabetes patients at all levels of health care [1]. Research must begin to evaluate the barriers that may keep older adults from receiving recommended care [2][3][4]. Diabetes selfcare activities such as diet, exercise, foot care, and self-glucose monitoring are considered a cornerstone to good diabetes care [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes Mellitus adalah penyakit kronis yang ditandai dengan tingginya kadar gula darah akibat kurangnya produksi insulin (hormon yang mengatur glukosa darah), menurunnya kerja insulin, atau keduanya (Shrivastva et al, 2019). Diabetes Mellitus juga merupakan salah satu penyakit tidak menular yang banyak terjadi di dunia maupun di Indonesia.…”
Section: Pendahuluanunclassified